Improving the quality of healthcare: a cross-sectional study of the features of successful clinical networks - Mary M Haines; Bernadette Brown; Catherine A D'Este; Elizabeth M Yano; Jonathan C Craig; Sandy Middleton; Peter A Castaldi; Carol A Pollock; Kate Needham; William H Watt; Elizabeth J Elliott; Anthony Scott; et al. (Sax Institute, 2018)
Objectives: Networks of clinical experts are being established internationally to help embed evidence based care in health systems. There is emerging evidence that these clinical networks can drive quality improvement programs, but the features that distinguish successful networks are largely unknown. We examined the factors that make clinical networks effective at improving quality of care and facilitating system-wide changes. Methods: We conducted a retrospective cross-sectional study of 19 state-wide clinical networks that reflected a range of medical and surgical specialty care and were in operation from 2006 to 2008 in New South Wales, Australia. We conducted qualitative interviews with network leaders to characterise potential impacts, and conducted internet surveys of network members to evaluate external support and the organisational and program characteristics of their respective networks. The main outcome measures were median ratings of individual network impacts on quality of care and system-wide changes, determined through independent assessment of documented evidence by an expert panel. Results: We interviewed 19 network managers and 32 network co-chairs; 592 network members completed internet surveys. Three networks were rated as having had high impact on quality of care, and seven as having had high impact on system-wide change. Better-perceived strategic and operational network management was significantly associated with higher ratings of impact on quality of care (coefficient estimate 0.86; 95% confidence interval [CI] 0.02, 1.69). Better-perceived leadership of the network manager (coefficient estimate 0.47; 95% CI 0.10, 0.85) and strategic and operational network management (coefficient estimate 0.23; 95% CI 0.06, 0.41) were associated with higher ratings of impact on system-wide change. Conclusions: This study represents the largest study of clinical networks undertaken to date. The results suggest that clinical networks that span the health system can improve quality of care and facilitate system-wide change. Network management and leadership, encompassing both strategic and operational elements at the organisational level, appear to be the primary influences on network success. These findings can guide future organisational and system-wide change programs and the development or strengthening of clinical networks to help implement evidence based care to improve service delivery and outcomes.